Study of cod removal by anaerobic digestion using mixed culture from sewage - Mohamad Fikhri, Burhanuddin (2010)
The purpose of this study is to investigate the application of mixed culture which was taken from the sewage to remove the chemical oxygen demand (COD) in the wastewater. Synthetic wastewater, which is glucose solution, was used in this study. Four different concentration of glucose, 1g/l, 2g/L 3g/L and 4g/L were used. This study attempts to reduce the concentration of COD in the glucose solution using biological treatment. The selected colony of bacteria which been grew on the agar plate was employed to the glucose solution for the anaerobic digestion to occur. The organic matter that contributed to COD will be degraded by the bacteria under anaerobic conditions using batch process. The experiment was run in the closed Schott bottle, which act as the anaerobic digester rig. Rubber tube was connected from the top of the Schott bottle to allow migrating of the biogas produced towards the water displacement unit for biogas collection. The experiment was conducted for five days of treatment time. The analysis on COD reduction percentage, turbidity reduction and observation on biogas production were conduct throughout this study. From the result obtained the glucose with concentration of 1g/L show the most COD reduction percentage which is 61.4%. The reduction percentages were decrease as the glucose concentration increased. The COD reduction for 2g/L of glucose was 50.55%, 38.88% for 3g/L of glucose and 31.28% for 4g/L of glucose. The turbidity for all glucose solution used also shows reducing trends. There is production of biogas during the anaerobic digestion process and was observed through the water displacement unit. Bubble built up in the water displacement unit represents the biogas that produced.